OPPORTUNITIES FOR DEVELOPING AGROTURISM IN BUKHARAREGION: ANALYSIS BASED ON STATISTICAL INDICATORS (World Economics and Finance Bulletin, 2026)
This article scientifically analyzes the opportunities for developing agritourism in the Bukhara region of Uzbekistan based on statistical indicators. The study examines the region's agricultural potential, tourism infrastructure, tourist flow dynamics, and the economic impact of agritourism. Using SWOT analysis and quantitative assessment methodology, the region's agritourism potential index was determined to be 0.68 (high potential). Karakul sheep-based unique tourism products, gastronomic agritourism, and handicraft integration were identified as the most promising directions. According to forecasts, with an effective strategy, it is possible to earn an annual income of $64 million from agritourism in Bukhara region by 2030 and create more than 2,500 jobs.
Keywords: agritourism; Bukhara region; Karakul sheep